Detection of flavonoids in Alpinia purpurata (Vieill.) K. Schum. leaves using high-performance liquid chromatography Detecção de flavonóides em folhas de Alpinia purpurata (Vieill.) K. Schum. por cromatografia líquida de alta eficiência - C.P. Victório; R.M. Kuster; C.L.S. Lage (Universidade Estadual Paulista, 2009)
The species Alpinia purpurata is scarcely cited as to ethnopharmacology and phytochemistry. This study aimed to analyze bioactive compounds through high-performance liquid chromatography (HPLC). Hydroalcoholic crude extract was obtained from A. purpurata dried leaves. Folin-Ciocalteau method was used to quantify total phenols, using gallic acid as standard. The obtained result was 15.6 mg GAE g-1. The crude extract was partitioned with the solvents ethyl acetate and butanol, followed by thin-layer chromatography (TLC) and HPLC. The flavonoids kaempferol-3-O-glucuronide and rutin were detected at a higher concentration in ethyl acetate and butanolic extracts. The butanolic extract contains the highest flavonoid percentage (94.3%). A. purpurata presents important flavonoids of therapeutic use, already verified for A. zerumbet. This is the first study verifying the presence of flavonoids in A. purpurata extracts. A espécie Alpinia purpurata apresenta poucas citações referentes a etnofarmacologia e fitoquímica. Este estudo propõe a análise de substâncias bioativas através da técnica de cromatografia líquida de alta eficiência (CLAE). O extrato bruto hidroalcóolico foi obtido a partir de folhas secas de A. purpurata. A quantificação de fenóis totais foi realizada pelo método de Folin-Ciocalteau, usando ácido gálico como padrão. Como resultado, foi verificado 15,6 mg EAG g-1. O extrato bruto foi particionado com os solventes acetato de etila e butanol e depois analisado por cromatografia em camada delgada e CLAE. Nos extratos acetato de etila e butanólico foi detectada a presença dos flavonóides kaempferol-3-O-glicuronídeo e rutina, em maior concentração. O extrato butanólico contém a maior porcentagem de flavonóides (94,3%). Esta espécie possui flavonóides importantes no uso terapêutico, já antes verificados para a espécie A. zerumbet. Este é o primeiro trabalho que verifica a presença de flavonóides em extratos de A. purpurata.